Digital technology and journalism: implications for Democracy - Pavlik, John V. (Brazilian journalism research, 2011)
Digital technology has brought sweeping changes to journalism and the social institutions it serves. Journalism has historically played a central role in the U.S. and other democracies, serving as a primary source of news and information for citizens on matters of public importance. This paper examines the implications of these changes for democracy. It explores the question of whether a more interactive form of journalism will produce a more engaged and informed electorate.